Changing Spectrum of Invasive Fungal Infections of the Anterior Skull Base - Bhuskute, Govind Shripad; Keshri, Amit Kumar; Seduchidambaram, Malathy; Dubey, Abhishek; Hameed, Nazrin; Chidambaram, Kalyan; Muraleedharan, Manjul; Das, Kuntal Kanti; Mehrotra, Anant; Srivastava, Arun; Jaiswal, Awadesh; Kumar, Raj; Manogaran, Ravi Sankar (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objective To study the etiological and anatomical factors in pathophysiology of invasive fungal rhinosinusitis affecting the skull base.Design Retrospective clinical study over 5 years.Setting Single-center tertiary referral hospital.Materials and Methods All cases of invasive fungal rhinosinusitis with clinicoradiological and/or operative evidence of anterior and central skull base, orbit, and orbital apex involvement with or without intracranial disease were included in the study. Patients with a sinonasal-palatal disease without the involvement of the skull base or orbit were excluded from the study. In addition, we assessed the risk factors such as coronavirus disease 2019 (COVID-19) infection, diabetes mellitus (DM), and other immunocompromised conditions.Results There were 79 patients, of which 65.8% had skull base rhino-oribitocerebral mucormycosis (ROCM), and 34.2% had Aspergillus infection. The mean duration from onset of the symptom to presentation of ROCM was 36.75 ± 20.97 days, while for the Aspergillus group was 21 weeks. The majority of patients (66%) with ROCM presented after 30 days of symptom onset. Among ROCM patients, 88.7% had a history of COVID-19 infection, and 96% had DM. In 40.8% of patients with Aspergillus infection, the tissue diagnosis was unavailable, and galactomannan assay and clinicoradiological assessment were used for diagnosis. The most common area of the skull base involved was the pterygopalatine fossa (88.5%), followed by the infratemporal fossa (73.1%). The most common neurovascular structure (75%) involved was the pterygopalatine ganglion and the infraorbital nerve.Conclusion With the increasing incidence of invasive fungal infections worldwide, particularly after the COVID-19 pandemic, it is crucial to understand the evolving nature of this disease. ROCM, documented in the literature to cause fulminant disease, became a chronic illness, possibly due to the improvement of the patient's immunity during the disease course.
Keywords: mucormycosis; aspergillosis; fungal sinusitis; invasive sinusitis; COVID-19